British national identity and the Anglo-American special relationship. (2nd July 2016) - Vucetic, Srdjan
Abstract : Why are successive UK governments so staunchly committed to the 'special relationship' with the US? One common answer – a part of an answer at least – evokes the role of identity and identification. The UK supports the US because the UK's ruling elite believe that the Americans and the British are birds of a feather. This article examines this hypothesis from a 'national identity as a variable' framework developed in constructivist International Relations theory. The main argument presented is that UK support for the special relationship is rooted not simply in elite beliefs but rather in a wider societal acceptance of the global hegemony of 'American' democratic neoliberalism. Multiple national identity discourses exist, but none of them calls on Westminster and Whitehall to chart a path that would be at odds with a world centred on Washington, DC.